Anterior Approach for Fixation of Acetabular Fractures Using Anatomically Designed Plates: Accuracy of Reduction and Early Functional Outcomes With a Minimum of 1-Year Follow-Up. Issue 9 (September 2022) - Khalefa, Mohamed A.; El Nahal, Walid A.; Abdel Karim, Mahmoud; Abdel-Kader, Khaled F. M.; Chesser, Timothy John Sloan; Ward, Anthony J.; Acharya, Mehool
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: To evaluate the results of a new plate system using anterior approaches in the management of acetabular fractures. Design: Retrospective case-note review. Setting: Pelvic and acetabular tertiary center. Patients and intervention: A consecutive series of acetabular fractures treated using only anterior approach and anatomical plates, at one tertiary specialist unit, were reviewed. The fracture patterns, incisions used, intraoperative and postoperative complications, reduction achieved (measured on postoperative radiographs and computed tomography scans), and early postoperative results (minimum 1-year follow-up) were recorded. Main Outcome measurement: Postoperative reduction (measured by postoperative plain radiographs and computed tomography). Results: Thirty-three patients (mean age, 57 years) underwent reconstruction with the anatomical plates using anterior approaches. Associated both columns and anterior column posterior hemitransverse represented most of the patients (85%). The fracture pattern was complex with quadrilateral plate involvement in 79% of cases. Overall, anatomic reduction was seen in 82% on plain radiographs and CT scan evaluation. Increasing age was a statistically significant variable in obtaining anatomical reduction with an age cutoff value of 70 years ( P 0.012). Associated both column fractures were associated with a lower incidence of anatomical reduction ( P = 0.038). Complication rates were comparable with the literature. 22 patients (71%) were symptom free, with 20 patients (62.5%) having excellent radiographic outcomes at the latest follow-up. Conclusions: The results suggested that using approach-specific instruments and anatomical plates through anterior approaches in a specialized unit led to anatomical reconstruction in 82% with patients demonstrating satisfactory early radiological and functional outcomes at 1 year. Level of Evidence: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.